Red mud-based ceramic flat sheet membrane loaded with MnO2 catalyst on surface and preparation method of red mud-based ceramic flat sheet membrane
The red mud-based ceramic membrane prepared by gradient sintering and high-pressure spraying with a red mud-based support solves the problems of high cost, complex separation layer preparation and single function of ceramic membranes, and achieves efficient separation and catalysis integration, reduces energy consumption and expands the application range.
Patent Information
- Application Number
- CN202511692567.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-03-13
AI Technical Summary
Existing ceramic membranes are expensive, have high sintering energy consumption, complex separation layer preparation and single function, making them difficult to effectively treat recalcitrant wastewater, and the catalyst is easily lost.
A separation layer was prepared by using a red mud-based support and gradient sintering process combined with a high-pressure spraying method. MnO2 catalyst was loaded on the surface of the separation layer to form an integrated membrane structure. By utilizing the resources of red mud, the cost was reduced, the pore size and flexural strength were optimized, and efficient separation and catalytic functions were achieved.
It significantly reduces the preparation cost of ceramic membranes, improves membrane permeability and selectivity, reduces catalyst loss, expands the application range for treating recalcitrant wastewater, and ensures the stability and efficiency of the process.
Smart Images

Figure CN121648757A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic membrane technology, specifically to a red mud-based ceramic flat sheet membrane with a surface-supported MnO2 catalyst and its preparation method. Background Technology
[0002] Against the backdrop of global water scarcity and the increasing demand for industrial separation, ceramic membranes have become a core material in the field of separation technology due to their high temperature resistance, corrosion resistance, and high mechanical strength. Compared with polymer membranes, the stability of ceramic membranes under extreme conditions (such as pH tolerance of 0-14 and high temperature environments above 500℃) makes them irreplaceable in energy, chemical and other fields.
[0003] The high cost of ceramic membranes is attributed to expensive raw materials, high sintering costs, and low recovery rates. The preparation of ceramic membranes involves multiple "sintering-coating-sintering" processes, requiring high sintering temperatures and long cycle times, thus increasing the overall cost. Studies have shown that the total cost of membrane manufacturing comprises three main components: material costs, sintering costs, and manufacturing process costs, accounting for 20%, 60%, and 20% of the total cost, respectively. Raw material and energy costs related to the sintering process are the primary factors contributing to the high price of ceramic membranes. Therefore, reducing sintering and raw material costs can effectively lower the overall cost of ceramic membranes. Furthermore, how to further improve the performance of ceramic membranes, specifically by controlling pore size and designing novel structures to enhance permeability and selectivity, remains a major goal of recent research.
[0004] Red mud, a by-product of the aluminum industry, causes serious environmental problems due to its high alkalinity and complex chemical composition (containing Fe2O3, Al2O3, SiO2, etc.) when stored for a long time. Its resource utilization has become a research hotspot in the field of environmental materials. In recent years, red mud has been used as a functional additive in the preparation of ceramic membranes, which can not only realize the resource utilization of solid waste, but also optimize the performance of membrane materials by utilizing its metal oxide components.
[0005] Current research on ceramic membranes is increasingly focusing on mitigating membrane fouling, improving membrane mechanical strength, increasing membrane flux, and enhancing selectivity. Ceramic membrane separation technology has been explored in various water treatment applications, including the treatment of phenol-containing wastewater, semiconductor industry wastewater, textile wastewater, oily wastewater, domestic sewage, and seawater desalination. Building upon this foundation, and to meet even higher water treatment targets, membrane separation technology faces greater challenges. Researchers have achieved some success by coupling membrane separation technology with other technologies to remove recalcitrant organic matter and mitigate membrane fouling. For example, for common secondary effluent, wastewater still contains certain substances such as bacterial flocs, sludge, and fine sand after primary and secondary treatment. If ceramic membranes are used for further wastewater treatment, it will cause serious irreversible fouling of the membrane pores. Therefore, using membrane separation technology alone is uneconomical. Membrane separation technology can be combined with ozone catalytic oxidation to remove recalcitrant wastewater. By pre-ozonating the wastewater, the content of colloidal and suspended organic matter in the wastewater can be reduced, thus reducing the operating pressure on the subsequent membrane separation stage. This demonstrates a good ability to reduce membrane fouling, wastewater color, and stubborn micropollutants. On the other hand, ceramic membranes can retain metal oxide catalysts, which plays an important role in reducing catalyst loss. The red mud-based ceramic membrane involved in this invention has the characteristics of high water discharge efficiency, stable structure and acid and alkali resistance, which can effectively achieve efficient retention and recovery of micro and nano catalysts, significantly reduce catalyst loss rate, and thus ensure continuous and stable operation of the process. It has high technical feasibility. Summary of the Invention
[0006] This invention aims to address the shortcomings of the aforementioned technologies while simultaneously achieving the resource utilization of solid waste. This invention provides a formulation and preparation process for a ceramic flat-sheet membrane, including a method for preparing a ceramic support, its separation layer, and a MnO2 catalyst supported layer. The ceramic membrane prepared according to the technical solution of this invention has a uniform pore size distribution, with an average pore size range of 170-220 nm, and a pure water flux of 2979.37 L / (h·m). 2 ・bar).
[0007] To achieve the above objectives, the present invention provides the following technical solution: A red mud-based ceramic flat sheet membrane with MnO2 catalyst supported on its surface includes a red mud-based support, a separation layer and an MnO2 catalyst support layer arranged sequentially. The raw materials of the red mud-based support include, by weight: 3-3.5 kg of Al2O3 powder, 270-300 g of corn starch, 420-450 g of red mud, 540-580 g of kaolin, 100-150 mL of 4 wt% PVA solution and 300-400 mL of ultrapure water. The raw materials of the separation layer, by weight, include: 6-8g of Al2O3 powder with an average particle size of 5000nm, 60-80mL of ultrapure water, 2-3g of dispersant, 0.2-0.3g of defoamer, and 30-40mL of 5.5wt% PVA solution; The MnO2 catalyst support layer is formed by reacting 30.1g ammonium persulfate, 22.3g manganese sulfate monohydrate, and 800-830mL of ultrapure water.
[0008] As a further technical solution, the red mud-based support has a pore size distribution of 81-1100nm, a porosity of 30-45%, and a flexural strength of 25-40MPa.
[0009] As a further technical solution, the pore size distribution of the separation layer is 170-220nm.
[0010] A method for preparing a red mud-based ceramic flat sheet membrane with a surface-supported MnO2 catalyst includes the following steps: (1) Preparation of red mud-based support: Al2O3 powder, corn starch, red mud and kaolin were mixed evenly for 20 min by a double motion mixer; 4 wt% PVA solution and ultrapure water were added dropwise to the mixed powder, and after being stirred evenly by hand, it was transferred to a kneader and kneaded continuously for 2 h, and then sealed and aged for 48 h; the aged mud was transferred to a high-pressure vacuum extruder and kneaded twice under a vacuum degree ≤0.10 MPa, and extruded into shape using a special mold for flat film at a speed of 0.50 mm / s and a pressure of 15 MPa; the extruded green body was cut and placed in a constant temperature and humidity drying oven at 60℃ and relative humidity of 5.00% for 48 h, with a final moisture content ≤1.50%; the dried green body was placed in a high-temperature box furnace for multi-point drying and furnace cooling to room temperature; (2) Separation layer formation: The red mud-based support was placed in deionized water, cleaned with an ultrasonic cleaner for 15 min, dried at 105℃ for 2 h, and then stored in a vacuum drying oven; Al2O3 powder with an average particle size of 5000 nm was dispersed in ultrapure water, a dispersant and a defoamer were added, and the mixture was ball-milled for 30 min in a planetary ball mill at a speed of 300-350 rpm and a ball-to-material ratio of 5-8:1, and then stirred in a magnetic stirrer at 500-550 rpm for 240 min, and then mixed with 5.5 Mix wt% PVA solution and let stand for 15 minutes to remove air bubbles; spray three times with a high-pressure spray gun at a distance of 20-25 cm, with 10-minute intervals between each spray; dry in a constant temperature and humidity drying oven at 60℃ and 40% relative humidity for 4 hours; place in a high-temperature box furnace and heat to 1100℃ at 1℃ / min and hold for 2 hours, then cool to room temperature; use epoxy resin AB glue to bond the film and end-capping components, and after standing for 24 hours, test the airtightness at 0.20 MPa; the leakage rate is ≤0.10%. (3) Formation of MnO2 support layer: The support containing the separation layer was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence. After rinsing with deionized water, it was dried at 80-85℃ for 6 h. Ammonium persulfate and manganese sulfate monohydrate were added to ultrapure water and magnetically stirred for 20 min to form a transparent solution. The solution was poured into 1000 mL of polytetrafluoroethylene liner. The support was placed vertically into the inner substrate and sealed in a high-temperature reactor. The reaction was carried out in a 120℃ constant temperature drying oven for 10 h. After the reaction was completed, the solution was naturally cooled to room temperature. The support was taken out and rinsed with deionized water and anhydrous ethanol in sequence. The solution was dried at 80-85℃ for 6 h to obtain the target membrane.
[0011] The reaction equation for this process is as follows: (NH4)2S2O8+MnSO4·H2O+H2O→MnO2+(NH4)2SO4+2H2SO4; As a further technical solution, in step (1), the PVA solution is continuously stirred for 2 hours under a water bath at 85-90℃ until it is completely dissolved, and then naturally cooled to room temperature.
[0012] As a further technical solution, the temperature of the extrusion mold in step (1) is 25±2℃, and the thickness deviation of the blank is ≤0.20mm.
[0013] As a further technical solution, the multi-point drying in step (1) is as follows: the temperature is increased to 300℃ at 2℃ / min and kept at 0.50h, then increased to 450℃ at 2℃ / min and kept at 0.50h, and then increased to 1100℃, 1200℃, 1250℃ and 1300℃ at 5℃ / min respectively and kept at each temperature point for 2h.
[0014] As a further technical solution, the ultrasonic cleaner in step (2) has a cleaning frequency of 40kHz and a power of 100W.
[0015] As a further technical solution, in step (2), the vacuum degree of the vacuum drying oven is ≤0.01MPa and the temperature is 25℃.
[0016] As a further technical solution, in step (2), the nozzle diameter of the high-pressure spray gun is 0.50 mm and the pressure is 0.30 MPa.
[0017] Compared with the prior art, the beneficial effects of the present invention are: To address the problems of high raw material costs for existing ceramic membranes, environmental pollution from red mud stockpiling, and structural inhomogeneity during support sintering, this invention introduces red mud into the support and employs a gradient sintering process, achieving synergistic optimization of solid waste resource utilization and support performance. From a microscopic perspective, red mud, as a byproduct of the aluminum industry, contains metal oxides such as Fe2O3 and Al2O3. When combined with kaolin, these oxides act as sintering aids, forming a low-temperature eutectic phase with Al2O3 aggregate, significantly reducing the activation energy of the sintering process and decreasing the energy input required for high-temperature sintering. Simultaneously, red mud replaces some traditional expensive sintering raw materials, directly reducing material costs at the source and achieving solid waste resource utilization, thus avoiding the environmental problems associated with long-term red mud stockpiling. By further combining gradient sintering process, microscopically, internal stress cracking caused by rapid temperature rise and fall in the green body can be avoided. The porosity (30-45%) and flexural strength (25-40MPa) of the support body are appropriate. The appropriate porosity ensures that the slurry penetrates moderately and does not block the pores of the support body during the subsequent coating of the separation layer, while the sufficient flexural strength ensures the mechanical stability of the membrane during use. This effectively solves the problem that traditional single sintering process cannot take into account both the permeability and strength of the support body.
[0018] To address the problems of high energy consumption, long cycle time, and difficulty in balancing membrane flux and selectivity caused by the need for multiple coatings and firings in the preparation of existing ceramic membrane separation layers, this invention prepares the separation layer using a high-pressure spraying method and optimizes the pore size matching and sealing process, achieving efficient preparation of the separation layer and improved membrane separation performance. At the microscopic level, the high-pressure spray gun enables the Al2O3 slurry to form a uniform coating on the support surface, and the design of three sprays spaced 10 minutes apart avoids cracking caused by continuous accumulation of the coating. Compared to the traditional multiple coating and firing process, this invention only requires a single firing step at 1100℃ for 2 hours, saving energy from repeated high-temperature sintering and avoiding the problem of pore blockage caused by over-sintering of the support due to repeated high temperatures. Meanwhile, the pore size gradient design of the support (81-1100nm) and the separation layer (170-220nm) can reduce concentration polarization during the separation process at the microscopic level, significantly improving the membrane permeate flux (pure water flux reaches 2979.37L / (h・m²・bar)), and the narrow pore size distribution of the separation layer ensures separation selectivity; subsequent AB glue sealing and airtightness testing (leakage rate ≤0.10%) ensure that the membrane module is leak-free, further ensuring separation efficiency, and ultimately solving the problems of "high energy consumption and long cycle" in traditional separation layer preparation and "flux-selectivity imbalance" in membranes.
[0019] To address the limitations of existing ceramic membranes, such as their single function, the need for additional catalytic equipment for treating recalcitrant wastewater, and the susceptibility of catalyst loss, this invention employs a hydrothermal method to load a MnO2 catalyst onto the separation layer surface. This, combined with the preceding support and separation layer design, creates a synergistic effect, achieving an integrated "separation-catalysis" function enhancement. Microscopically, ammonium persulfate and manganese sulfate monohydrate undergo a redox reaction at 120°C hydrothermally, allowing MnO2 to grow uniformly on the membrane surface. Its catalytic activity directly oxidizes and decomposes recalcitrant organic matter in wastewater without the need for additional catalytic equipment, expanding the membrane's application range in complex water treatment scenarios such as phenol-containing wastewater and textile wastewater. Simultaneously, the inherent high-temperature resistance and corrosion resistance of the red mud-based ceramic membrane effectively retain the MnO2 catalyst, avoiding secondary pollution and cost waste caused by catalyst loss in traditional processes.
[0020] Instruction manual illustrations Figure 1 These are firing diagrams of ceramic membrane flat sheet supports at different temperatures; Figure 2 These are scanning electron microscope images of the ceramic flat film support at different temperatures (a. 1100℃, b. 1200℃, c. 1250℃, d. 1300℃) of the present invention. Figure 3 These are scanning electron microscope images of the ceramic flat sheet membrane separation layer in this invention (a. 100x surface magnification, b. 250x surface magnification, c. 1500x surface magnification, d. 130x cross-sectional magnification). Figure 4 These are comparative photographs of the appearance of the red mud-based ceramic flat plate membrane with MnO2 catalyst supported on the surface, as an example of the present invention (a. red mud-based substrate, b. Al2O3 separation layer membrane, c. red mud-based ceramic flat plate membrane with MnO2 catalyst supported on the surface). Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1 A red mud-based ceramic flat sheet membrane includes a support, a separation layer, and a MnO2 catalyst supported layer. The raw materials are shown in the table below: Table 1 Specifications of Support Materials Table 2 Specifications of raw materials for the separation layer Table 3 Specifications of MnO2 catalyst support layer This example also provides a method for preparing a red mud-based ceramic flat sheet membrane, including the following steps: Step 1: Prepare the ceramic flat sheet membrane support according to the raw material usage in Table 1; Step 1.1, Pretreatment of raw materials: Polyvinyl alcohol (PVA) was mixed with ultrapure water to prepare a 4wt% PVA solution. The solution was stirred continuously in a water bath at 85-90℃ for 2 hours until completely dissolved, then allowed to cool naturally to room temperature. Al2O3 powder (3kg) was used as aggregate, corn starch (270g) as a pore-forming agent, and red mud and kaolin were combined at a mass ratio of 0.75:1 (420g:540g) as a sintering aid. The mixture was uniformly mixed for 20 minutes using a double-motion mixer. Then, 100mL of the 4wt% PVA solution and 300mL of ultrapure water were added dropwise to the mixed powder. After uniform mixing by manual stirring, the mixture was transferred to a kneader and kneaded continuously for 2 hours. Once the material formed a homogeneous agglomerate structure, it was sealed in the kneader and aged for 48 hours to improve the plasticity of the clay. Step 1.2, Preparation of the support: The aged mud was transferred to a high-pressure vacuum extruder and kneaded a second time under a vacuum of ≤0.10MPa to completely eliminate internal air bubbles. A special die for flat film was used, and continuous extrusion was performed at a constant rate (0.50mm / s) and pressure (15MPa) via a screw extrusion mechanism. The die temperature was monitored in real time during extrusion (25±2℃) to ensure the dimensional accuracy of the formed preform (thickness deviation ≤0.20mm). After mechanical cutting and trimming, the extruded preform was placed in a constant temperature and humidity drying oven (60℃, relative humidity 5.00%) for 48 hours, with the final moisture content controlled below 1.50%. Step 1.3, Support Firing Process: The dried green body was placed in a high-temperature box furnace and subjected to a multi-stage temperature-controlled sintering process: the temperature was increased to 300℃ at a rate of 2℃ / min and held for 0.50h, then increased to 450℃ at a rate of 2℃ / min and held for 0.50h to completely decompose organic matter; subsequently, the temperature was increased to 1100℃, 1200℃, 1250℃ and 1300℃ at a rate of 5℃ / min, and held for 2h at each temperature to achieve phase transformation and densification; finally, the temperature was cooled to room temperature by furnace cooling. This gradient sintering strategy effectively controls key performance parameters of the ceramic matrix, such as porosity (30-45%) and flexural strength (25-40MPa). Step 2: Prepare the separation layer according to the raw material usage in Table 2; Step 2.1, Pre-treatment of the support structure: The support was placed in deionized water and cleaned for 15 minutes using an ultrasonic cleaner (frequency 40kHz, power 100W) to remove residual particles and contaminants from the surface. After cleaning, the support was transferred to a forced-air drying oven and dried at 105℃ for 2 hours to ensure no moisture residue remained on the surface. Subsequently, the dried support was stored in a vacuum drying oven (vacuum degree ≤0.01MPa, temperature 25℃) to avoid environmental moisture and dust contamination, ensuring the surface cleanliness of the support met the requirements for subsequent coating. Step 2.2, Preparation of the separation layer slurry: The separation layer slurry was prepared by mixing a catalyst dispersion and a binder. First, 6g of Al2O3 powder (average particle size 5000nm) was uniformly dispersed in 60mL of ultrapure water. Then, 2g of dispersant and 0.2g of defoamer were added sequentially, and the mixture was ball-milled for 30min using a planetary ball mill (300rpm, ball-to-powder ratio 5:1) to obtain a uniformly dispersed Al2O3 suspension. Next, a 5.50wt% polyvinyl alcohol (PVA) solution was prepared as a binder. 30mL of the 5.5wt% PVA solution was measured and mixed with the Al2O3 suspension. The mixture was continuously stirred in a magnetic stirrer (500rpm) for 240min to ensure uniformity and stability. Finally, the mixed slurry was allowed to stand for 15min to eliminate air bubbles, resulting in a homogeneous separation layer slurry. Step 2.3, Spraying the release layer: The coating liquid was evenly sprayed onto the pretreated support surface using a high-pressure spray gun (nozzle diameter 0.50 mm, pressure 0.30 MPa). The spraying distance was controlled at 20 cm, and the coating was applied three times with a 10-minute interval between each application to ensure that the previous coating was fully dry. After spraying, the sample was transferred to a constant temperature and humidity drying oven (temperature 60℃, relative humidity 40%) for 4 hours to allow the coating to initially cure. Step 2.4, Firing Process: The dried coating support was placed in a high-temperature box furnace and heated to 1100℃ at a heating rate of 1℃ / min, and held at that temperature for 2 hours to achieve coating densification and crystal phase stabilization. It was then allowed to cool naturally to room temperature with the furnace. This firing process can effectively control the porosity of the film. Step 2.5, Sealing: The fired ceramic membrane was bonded to the membrane end-cap assembly using AB adhesive (epoxy resin-based), and allowed to stand for 24 hours to ensure complete curing of the adhesive layer. An airtightness tester (test pressure 0.20 MPa) was used to test the airtightness of the assembled ceramic membrane. If any leaks were found, they were repaired using a localized adhesive patching method, and the test was repeated until the airtightness met the standard (leakage rate ≤0.10%).
[0023] Step 3: Prepare the MnO2 catalyst support layer according to the raw material usage in Table 3; Step 3.1, Al2O3 ceramic membrane pretreatment: First, the prepared red mud-based Al2O3 blank ceramic substrate film was washed with tap water, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence. Then it was taken out, rinsed with deionized water, and placed in an 80℃ constant temperature drying oven for 6 h to dry for later use.
[0024] Step 3.2: Preparation of red mud-based ceramic flat plate composite membrane with MnO2 catalyst supported on surface by hydrothermal method 30.1 g of ammonium persulfate ((NH4)2S2O8) and 20.3 g of manganese sulfate monohydrate (MnSO4·H2O) were taken and added to 800 mL of deionized water. The mixture was magnetically stirred for 20 min to form a transparent solution, which was then poured into a 1000 mL polytetrafluoroethylene (PTFE) liner. Simultaneously, a blank red mud-based Al2O3 ceramic substrate film was vertically placed onto the inner substrate. Finally, the PTFE liner was placed in a high-temperature reactor, sealed, and placed in a 120°C constant temperature drying oven for 10 h. The reaction equations for this process are as follows: (NH4)2S2O8+MnSO4·H2O+H2O→MnO2+(NH4)2SO4+2H2SO4; After the reaction is complete, remove the high-temperature reactor and allow it to cool naturally to room temperature. Remove the blank red mud-based Al2O3 ceramic substrate membrane from the liner, rinse it with deionized water and anhydrous ethanol in sequence, and then place it in an 80℃ constant temperature drying oven for 6 hours to obtain a red mud-based ceramic flat plate composite membrane with MnO2 catalyst loaded on its surface.
[0025] The ceramic membrane prepared according to the technical solution of Example 1 has a uniform pore size distribution, with an average pore size range of 170-220 nm, and a pure water flux of 2979.37 L / (h·m). 2 ・bar).
[0026] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not describe all details exhaustively, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification.
Claims
1. A red mud-based ceramic flat sheet membrane with a surface-supported MnO2 catalyst, characterized in that, It includes a red mud-based support, a separation layer, and a MnO2 catalyst support layer arranged sequentially; The raw materials of the red mud-based support include, by weight: 3-3.5 kg of Al2O3 powder, 270-300 g of corn starch, 420-450 g of red mud, 540-580 g of kaolin, 100-150 mL of 4 wt% PVA solution and 300-400 mL of ultrapure water. The raw materials of the separation layer, by weight, include: 6-8g of Al2O3 powder with an average particle size of 5000nm, 60-80mL of ultrapure water, 2-3g of dispersant, 0.2-0.3g of defoamer, and 30-40mL of 5.5wt% PVA solution; The MnO2 catalyst support layer is formed by reacting 30.1g ammonium persulfate, 22.3g manganese sulfate monohydrate, and 800-830mL of ultrapure water.
2. The red mud-based ceramic flat sheet membrane with surface-supported MnO2 catalyst according to claim 1, characterized in that, The red mud-based support has a pore size distribution of 81-1100 nm, a porosity of 30-45%, and a flexural strength of 25-40 MPa.
3. The red mud-based ceramic flat sheet membrane with surface-supported MnO2 catalyst according to claim 1, characterized in that, The pore size distribution of the separation layer is 170-220 nm.
4. A method for preparing a red mud-based ceramic flat sheet membrane with a surface-supported MnO2 catalyst according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Preparation of red mud-based support: Al2O3 powder, corn starch, red mud and kaolin were mixed evenly for 20 min by a double motion mixer; 4 wt% PVA solution and ultrapure water were added dropwise to the mixed powder, and after being stirred evenly by hand, it was transferred to a kneader and kneaded continuously for 2 h, and then sealed and aged for 48 h; the aged mud was transferred to a high-pressure vacuum extruder and kneaded twice under a vacuum degree ≤0.10 MPa, and extruded into shape using a special mold for flat film at a speed of 0.50 mm / s and a pressure of 15 MPa; the extruded green body was cut and placed in a constant temperature and humidity drying oven at 60℃ and relative humidity of 5.00% for 48 h, with a final moisture content ≤1.50%; the dried green body was placed in a high-temperature box furnace for multi-point drying and furnace cooling to room temperature; (2) Separation layer formation: The red mud-based support was placed in deionized water, cleaned with an ultrasonic cleaner for 15 min, dried at 105℃ for 2 h, and then stored in a vacuum drying oven; Al2O3 powder with an average particle size of 5000 nm was dispersed in ultrapure water, a dispersant and a defoamer were added, and the mixture was ball-milled for 30 min in a planetary ball mill at a speed of 300-350 rpm and a ball-to-material ratio of 5-8:1, and then stirred in a magnetic stirrer at 500-550 rpm for 240 min, and then mixed with 5.5 Mix wt% PVA solution and let stand for 15 minutes to remove air bubbles; spray three times with a high-pressure spray gun at a distance of 20-25 cm, with 10-minute intervals between each spray; dry in a constant temperature and humidity drying oven at 60℃ and 40% relative humidity for 4 hours; place in a high-temperature box furnace and heat to 1100℃ at 1℃ / min and hold for 2 hours, then cool to room temperature; use epoxy resin AB glue to bond the film and end-capping components, and after standing for 24 hours, test the airtightness at 0.20 MPa; the leakage rate is ≤0.10%. (3) Formation of MnO2 support layer: The support containing the separation layer was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence. After rinsing with deionized water, it was dried at 80-85℃ for 6 h. Ammonium persulfate and manganese sulfate monohydrate were added to ultrapure water and magnetically stirred for 20 min to form a transparent solution. The solution was poured into 1000 mL of polytetrafluoroethylene liner. The support was placed vertically into the inner substrate and sealed in a high-temperature reactor. The reaction was carried out in a 120℃ constant temperature drying oven for 10 h. After the reaction was completed, the solution was naturally cooled to room temperature. The support was taken out and rinsed with deionized water and anhydrous ethanol in sequence. The solution was dried at 80-85℃ for 6 h to obtain the target membrane.
5. The preparation method according to claim 4, characterized in that, In step (1), the PVA solution is prepared by stirring continuously for 2 hours under a water bath at 85-90℃ until it is completely dissolved, and then naturally cooled to room temperature.
6. The preparation method according to claim 4, characterized in that, In step (1), the temperature of the extrusion mold is 25±2℃ and the thickness deviation of the blank is ≤0.20mm.
7. The preparation method according to claim 4, characterized in that, The multi-point drying in step (1) is as follows: the temperature is increased to 300℃ at 2℃ / min and held for 0.50h, then increased to 450℃ at 2℃ / min and held for 0.50h, and then increased to 1100℃, 1200℃, 1250℃ and 1300℃ at 5℃ / min respectively and held for 2h at each temperature point.
8. The preparation method according to claim 4, characterized in that, In step (2), the ultrasonic cleaner operates at a frequency of 40kHz and a power of 100W.
9. The preparation method according to claim 4, characterized in that, In step (2), the vacuum degree of the vacuum drying oven is ≤0.01MPa and the temperature is 25℃.
10. The preparation method according to claim 4, characterized in that, In step (2), the nozzle diameter of the high-pressure spray gun is 0.50 mm and the pressure is 0.30 MPa.